Influence of Parenting Styles on the Academic Performance of Secondary School Students in Ethiope East Local Government Area Delta State - Obiunu, Rev FR DR Jude J. (International Journal of Educational Technology and Learning, 2018)
This study investigated the influence of parenting styles on academic performance of students in Ethiope East Local Government Area of Delta State, Nigeria. Three research hypotheses were formulated to guide the study. Several Literatures that are related to this study were reviewed. One hundred and twenty (120) copies of questionnaire were administered to one hundred and twenty (120) sampled students from four (4) secondary schools to generate data. Their responses were tallied and put in frequency tables and the Pearson Product Moment Correlation Co-efficient (r) was used for the analysis. The findings indicated the following: that there is no significant relationship between authoritarian parenting style and academic performance of secondary school students. Secondly, that there is no significant relationship between permissive parenting style and academic performance of secondary school students. Finally, that there is a significant relationship between authoritative parenting style and academic performance of secondary school students. Based on the findings, it was concluded that parenting styles have some measure of influence on the academic performance of secondary school children. This is because parents set goals and dictate the pace at which such children should go in most cases in the sampled population. For further studies and necessary action, some recommendations were made. Parents should be encouraged to use reinforcers to motivate children towards academic excellence. Secondly, parents should be directly involved in the educational process of their children. Finally, children should be given some measure of freedom to exercise their creative and learning potentials to think for themselves and take some decisions.